Analisa Kebutuhan Tenaga Rekam Medis Berdasarkan Beban Kerja dengan Metode ABK-Kes di Bagian Case Mix Rumah Sakit X Palembang Tahun 2021 - Hadi Priatmoko; Yuyun Yunengsih; Sali Setiatin (Jurnal Health Sains, 2021)
The role of coders is important for hospitals. The available coders to achieve harmony in a job. As a process to get the number of hours of work needed to complete the workload in a certain time an analysis of the workload is needed.This study was conducted to calculate the number of PMIK personnel needed at Hospital X Palembang according to workload analysis. This was a descriptive study with qualitative approach. Data collection is using observation and interview to the Coder employee at X Hospital Palembang.The education qualification of Coder employees at X Hospital Palembang are 4 (four) PMIK with Associate’s Degree of Medical Records. Human Resources SDM of SIK’s calculation (Case Mix) uses the medical workload analysis (ABK-Kes) method are 4 (four) PMIK and at X Hospital Palembang there are 4 (four) PMIK, so that the amount is still relatively safe to complete tasks according to the existing workload. The conclusion of this study is the number of PMIK coders in Hospital X Palembang there are 4 (four) PMIK coders. Calculation of HRK needs in the SIK (Case Mix) section using the Health Workload Analysis (ABK-Kes) method of 4 (four) PMIK and in X Palembang Hospital there are 4 (four) PMIK so that the number of officers is still relatively safe to complete tasks according to existing workloads.